Unprovoked atrial tachyarrhythmias in aging spontaneously hypertensive rats: the role of the autonomic nervous system - Scridon, Alina; Gallet, Clément; Arisha, Moussa M.; Oréa, Valérie; Chapuis, Bruno; Li, Na; Tabib, Alain; Christé, Georges; Barrès, Christian; Julien, Claude; Chevalier, Philippe (American journal of physiology. Heart and circulatory physiology, 2012)
Experimental models of unprovoked atrial tachyarrhythmias (AT) in conscious, ambulatory animals are lacking. We hypothesized that the aging, spontaneously hypertensive rat (SHR) may provide such a model. Baseline ECG recordings were acquired with radiotelemetry in eight young (14-wk-old) and eight aging (55-wk-old) SHRs and in two groups of four age-matched Wistar-Kyoto (WKY) rats. Quantification of AT and heart rate variability (HRV) analysis were performed based on 24-h ECG recordings in unrestrained rats. All animals were submitted to an emotional stress protocol (air-jet). In SHRs, carbamylcholine injections were also performed. Spontaneous AT episodes were observed in all eight aging SHRs (median, 91.5; range, 4–444 episodes/24 h), but not in young SHRs or WKY rats. HRV analysis demonstrated significantly decreased low frequency components in aging SHRs compared with age-matched WKY rats ( P < 0.01) and decreased low/high frequency ratios in both young ( P < 0.01) and aging ( P = 0.01) SHRs compared with normotensive controls. In aging SHRs, emotional stress significantly reduced the number of arrhythmic events, whereas carbamylcholine triggered AT and significantly increased atrial electrical instability. This study reports the occurrence of unprovoked episodes of atrial arrhythmia in hypertensive rats, and their increased incidence with aging. Our results suggest that autonomic imbalance with relative vagal hyperactivity may be responsible for the increased atrial arrhythmogenicity observed in this model. We also provide evidence that, in this model, the sympatho-vagal imbalance preceded the occurrence of arrhythmia. These results indicate that aging SHRs may provide valuable insight into the understanding of atrial arrhythmias.